Analisis Faktor Determinan Kejadian Gizi Kurang pada Batita Usia 6–23 Bulan di Puskesmas Nelayan Gresik - Diska Winda Putri; Diani Octaviyanti Handajani (IJMT : Indonesian Journal of Midwifery Today, 2026)
Background: Undernutrition among toddlers remains a major public health problem in Indonesia because it affects child growth, development, and future human resource quality. Several factors related to undernutrition include maternal knowledge, maternal education, family support, and complementary feeding practices. Objective: To analyze factors associated with undernutrition among toddlers at Puskesmas Nelayan Gresik. Method: This study used an analytic observational design with a cross-sectional approach. The population consisted of 70 mothers who had toddlers aged 6–23 months. A total of 55 respondents were selected using simple random sampling. Independent variables included maternal knowledge, maternal education, family support, and complementary feeding practices, while the dependent variable was toddler nutritional status. Data were collected using validated questionnaires and analyzed using ordinal regression with a significance level of 0.05. Results: Most respondents had poor knowledge (58.2%), secondary education level (78.2%), less supportive family support (45.5%), and adequate complementary feeding practices (58.2%). Statistical analysis showed that maternal knowledge (p = 0.000), family support (p = 0.010), and complementary feeding practices (p = 0.008) were significantly associated with undernutrition among toddlers. Maternal education was not significantly associated with undernutrition (p = 0.933). Conclusion: Maternal knowledge, family support, and complementary feeding practices were significantly associated with undernutrition among toddlers. Strengthening nutrition education and family involvement is recommended to prevent undernutrition.